Changes in Sleep Difficulties During the Transition to Statutory Retirement - Saana Myllyntausta; Paula Salo; Erkki Kronholm; Jaana Pentti; Mika Kivimäki; Jussi Vahtera; Sari Stenholm (Oxford University Press, 2025)
Study Objectives
This study examined changes in sleep during the transition from full-time work to statutory retirement. Both the prevalence of any sleep difficulty and the prevalence of specific sleep difficulties, such as difficulties falling asleep, difficulties maintaining sleep, waking up too early in the morning, and nonrestorative sleep, were examined.
Methods
Data from the Finnish Public Sector study were used. The study population consisted of 5,807 Finnish public sector employees who retired on statutory basis between 2000 and 2011. The participants responded on the Jenkins Sleep Problem Scale Questionnaire before and after retirement in surveys conducted every 4 years.
Results
At the last study wave before retirement, 30% of the participants had sleep difficulties. Prevalence of any sleep difficulty decreased during the retirement transition: the risk ratio (RR) for having sleep difficulties in the first study wave following retirement compared with the last study wave preceding retirement was 0.89 (95% confidence interval [CI] 0.85–0.94). During the retirement transition, both waking up too early in the morning (RR = 0.76, 95% CI 0.69–0.82) and nonrestorative sleep (RR = 0.47, 95% CI 0.42–0.53) decreased, whereas there was no change in difficulties falling asleep or difficulties maintaining sleep. The decreases in sleep difficulties occurred primarily among those with psychological distress, suboptimal self-rated health, short sleep duration, and job strain before retirement.
Conclusions
These longitudinal data suggest that transition to statutory retirement is associated with a decrease in sleep difficulties, especially waking up too early in the morning and nonrestorative sleep.